copia-like retrotransposons are ubiquitous among plants - Voytas, D. F.; Michael P. Cummings; Koniczny, A.; Ausubel, F. M.; Rodermel, S. R. (Proc Natl Acad Sci USAProc Natl Acad Sci USA, 1992)
Transposable genetic elements are assumed to be a feature of all eukaryotic genomes. Their identification, however, has largely been haphazard, limited principally to organisms subjected to molecular or genetic scrutiny. We assessed the phylogenetic distribution of copia-like retrotransposons, a class of transposable element that proliferates by reverse transcription, using a polymerase chain reaction assay designed to detect copia-like element reverse transcriptase sequences. copia-like retrotransposons were identified in 64 plant species as well as the photosynthetic protist Volvox carteri. The plant species included representatives from 9 of 10 plant divisions, including bryophytes, lycopods, ferns, gymnosperms, and angiosperms. DNA sequence analysis of 29 cloned PCR products and of a maize retrotransposon cDNA confirmed the identity of these sequences as copia-like reverse transcriptase sequences, thereby demonstrating that this class of retrotransposons is a ubiquitous component of plant genomes.